Heavy Metals 2018
DOI: 10.5772/intechopen.75722
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Response of Plants Grown under Heavy Metal Toxicity

Abstract: Sorghum vulgare L. plants when exposed to cadmium nitrate with the concentrations of 70 and 150 ppm per kg of soil for 90 days exhibited phytotoxic responses. The observations of specific responses were dependent on treatment combinations. The significant hazardous effects and oxidative damage of cadmium nitrate (70 and 150 ppm) were evident by increased MDA content and hydrogen peroxide content. However, these responses were reversed by exogenous application of putrescine (2.5 and 5.0 mM) and mycorrhiza (Glom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 91 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…The absorbance was recorded at 532 nm and 600 nm using a UV/visible spectrophotometer (Shimadzu UV-1201, Kyoto, Japan). The concentration of MDA was determined using Beer and Lambert’s equation [ 63 ].…”
Section: Methodsmentioning
confidence: 99%
“…The absorbance was recorded at 532 nm and 600 nm using a UV/visible spectrophotometer (Shimadzu UV-1201, Kyoto, Japan). The concentration of MDA was determined using Beer and Lambert’s equation [ 63 ].…”
Section: Methodsmentioning
confidence: 99%
“…So, the biomass of the plant was significantly ( p ≤ 0.01) decreased (Muro-González et al, 2020 ). According to Kumar and Pathak ( 2018 ), physiological as well as structural changes in different plants are caused by heavy metals stress (As, Pb, Cu, Cr, and Hg). However, ZnBc and CP-silica gel along with B3 significantly ( p ≤ 0.01) enhanced the FW and DW in all plant parts ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a dry oven, the mixture was heated for 30 min at 95°C and then cooled at freezing temperature. A spectrophotometer was used to measure the absorbance of the mixture at 532 nm and 600 nm wavelengths and by using Beer and Lambert's equation, the concentration of MDA in μmol g −1 was calculated (Kumar and Pathak, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the stress of heavy metals (Cr, Ni, Cd, Mn, As, Pb, Cu, and Hg) induce oxidative stress through uncontrolled production of ROS, which ultimately decreases chlorophyll content and overall growth of plants by suppressing the activities of enzymes (SOD, APX, and CAT), proteins, and phenolic compounds (Rehman et al, 2021). Similarly, Kumar and Pathak (2018) observed that Cu, Pb, Hg, Cr, and As cause structural and physiological changes in plants. However, the applications of CFOP, FOP + BT, and BN significantly (P < 0.01) regulated Cr and Pb ions in the Solanum melongena L. (Figure 3).…”
Section: Discussionmentioning
confidence: 99%